REFLECTIONS ON THE REALITY OF PANDEMIC AND ENVIRONMENTAL LAW (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
The changes imposed by the pandemic are detected in a process of intense changes in the entire Brazilian legal body. Being a global pandemic and bringing intense administrative and legislative changes, for reasons of precaution and urgency, to national and global state rules. Thus, the study becomes necessary and delimits the problem within the theoretical point of view of the present study. The work was based on the changes that took place in the services of environmental protection bodies, during the period of public calamity decreed at the federal and state levels. The investigation aimed to analyze how proposals and measures applicable in the national territory, especially, to address their most relevant changes, within the legal paradigm and Brazilian environmental law.